External short circuit-assisted proton conducting ceramic membrane for H2 permeation - Zhang, K.; Sunarso, J.; Pham, Gia; Wang, Shaobin; Liu, Shaomin (Elsevier Science Ltd, 2014)
Hydrogen permeation membrane is one of the key technologies enabling sustainable hydrogen production from hydrocarbon resources.The employment of such a membrane reactor allows simultaneous coupling of reaction and separation in one unit. This work studied the hydrogen permeation performance of external short circuit-assisted proton conducting BaZr0.1Ce0.2Y0.7O3-d (BZCY) and BaZr0.3Ce0.6Y0.1Zn0.05O3-d(BZCYZn) perovskite membranes. In general ,the lower electronic conductivity of these proton conducting perovskite membranes restricts the overall transport process. As such, we hypothesize that an external short circuit may be employed to provide the necessary electronic conductivity and thus improve the overall transport performance. Experimental results confirmed that the use of an external short circuit can improve the H2 fluxes through the proton conducting membranes. The presence of water vapor in the feed and the permeate stream also improved the fluxes slightly, probably due to the enhanced surfaceexchange processes on the membrane surface.To probe the practical value of both membranes, permeation tests for four hours were carried out in different gas conditions at high temperature. The test results demonstrated BZCYZn has superior stability with respect to BZCY.